Development of Interactive Multimedia-Based Learning Media Using Adobe Animate to Improve Student Learning Achievement at State Vocational High School 6 Kupang - Crispinus Paulus Tamal; Louis Ferdinan Boesday; Abdi Kurniawan Radja (Information Technology Education Journal, 2025)
This study aims to determine the procedure for developing interactive multimedia learning media applications using macromedia flash on the competency standard for assembling personal computers and to determine how much improvement in student learning achievement is using interactive multimedia learning media. This study uses development and experiment methods. The development model used is the development model according to Luther which consists of six stages, namely concept, design, material collecting, assembly, testing and distribution. Experiments are used to analyze the effectiveness of research products, which can be measured by looking at the difference between the pretest and posttest scores achieved by students. The data collection technique uses non-tests in the form of questionnaires to test the quality of learning media including usefulness, appearance/interface, interaction and independent learning using the linkert scale. Meanwhile, to test the effectiveness of the research product, a test is used in the form of a learning outcome test (achievement test) by conducting a pretest and posttest to measure the improvement in student learning achievement. The results of this study have produced learning media in the form of learning CDs on the competency standard for assembling personal computers by going through 5 stages of development procedures, namely concept, design, material collecting, assembly and testing. The results of the validation of learning media by material experts were 83.82% which was categorized as very feasible criteria, media experts were 86.85% which was categorized as very feasible criteria. The pretest results obtained an average value of 73.12 while the posttest obtained an average value of 84.18, classical completeness of 97.05% with a calculated t value of 14.807 > t table 1.69092.